Below knee long stump guillotine amputation for mine blast injury foot: a safe need to do primary management in war zone: an experience in 18 cases over 10 months - Ray, M. S.; Deepak, B. S. (International Surgery Journal, 2017)
Background:Somewhere in western sector, high intensity conflict zone, we had to manage a large number of battle causalities, especially gunshot wound abdomen, and mine blast injury foot. In our collective experience of working in battle strife- zone, we realized that the best and the least a surgical team can do is to execute an old fashioned ‘long stump’ below knee (BK) guillotine amputation, achieve perfect hemostasis, immobilize the limb and rapidly transport the patient to higher surgical centre. This increase in the magnitude of mine blast injuries prompted us to highlight the problem and its management. Methods: We analyzed 18 cases of anti- personnel mine blast injury foot over a 10 months period 2000 to 2001. We have managed 18 mine blast feet in “staged- manner. Stage I- “on battle-field” long stump BK guillotine amputation, perfect hemostasis, wound toileting and stump immobilization. Stage II - at a higher surgical centre elsewhere, the patient underwent a planned BK, prosthetic compatible, posterior myo-cutaneous flap covered stump construction and stage III - On recovery the patient with healed BK stump was transferred to limb prosthesis centre where tailor made BK prosthesis was provided and patient rehabilitated. Results:Various body regions were involved in the mine blast injuries, but the main brunt was borne by feet and legs followed by multiple body regions due to splinters. 18 patients underwent below knee (BK) amputation while 01patient required bilateral BK amputations. The initial aggressive BK Guillotine amputation saved the limb and life of all patients. Few had stump related self-limiting complications. Some had post-traumatic stress disorder (PTSD). Almost all of them had high degree of BK prosthesis acceptance. Conclusions:Mine blast causes extensive injuries and psychological trauma. Management is needed urgently, surgery is difficult, and amputation is often inevitable. In our experience on 18 cases this “safe-need-to-do” staged management of mine blast injury foot, in high conflict area, was found to be least time consuming, less precious resource draining and hardly manpower straining strategy.